Appraising Voices on Quora: Engagement Realizations in Discussions of the Sandwich Generation Phenomenon - Marwito Wihadi; Fahrus Zaman Fadhly; Aulia Apriliani (Journal of Language and Literature, 2026)
Engagement is now widely found on social media such as Quora, which contains various user perspectives on social issues. However, studies on the application of Engagement in discussions about the sandwich generation on Quora are still limited. The term sandwich generation is widely discussed nowadays. It is a condition where a child who has worked must become the breadwinner of the family where all of his/her income is given to meet household needs. This research examined the Engagement used by Quora users concerning the sandwich generation phenomenon. This research aimed to determine sub-categories of Engagement and analyze their functions used by 100 Quora users. Qualitative method used for this research with used discourse analysis approach and document analysis as research instrument. The result showed that there were 769 clauses containing the sub-categories of Engagement. The functions of Engagement sub-categories included monogloss to express a direct statement, deny to refute a statement directly, counter to oppose a statement by providing another statement, concur to show agreement, pronounce to give a strong statement, endorse to support viewpoint, entertain to open up discussion, acknowledge to refer to the external source, and distance to give distance with other viewpoints. Sandwich generation users tended to reject viewpoints related to this phenomenon, while non-sandwich generation users tended to open discussion spaces related to differences of viewpoints with other users.